SEJARAH DAN ARKEOLOGI MADURAÂ·BARAT ABAD XIV-XVIII: SEBUAH PENGENALAN TENTANG PENGUASANYA - Koestoro, Lucas Partanda (Berkala Arkeologi, 1995)
One interesting aspect related to the archaeological remains on the island of Madura is the relationship of the characters behind them with the historical journey that colored them. By regulating the views on the existence of various "legacies" of the past in West Madura, it is hoped that incentives will emerge to better recognize the various things they contain, namely the relationship between Madura and Java.